Proposed Use of a Polyvinyl Alcohol with Grape Pomace Extract as an Edible Coating for Strawberries - Gulce Bedis Kaynarca; Deniz Damla Altan Kamer; Emel Yucel; Tuncay Gümüş (Polish Journal of Food and Nutrition Sciences)
Strawberries rich nutrition, flavor, and aroma profiles make them popular. Many studies have tried to extend strawberries shelf life. In the current study, grape pomace extract (GPE) was combined with polyvinyl alcohol (PVA) and used to extend the shelf life of strawberries. Ascorbic acid content, total phenolic content, total anthocyanin content, and antioxidant activity determinations showed that PVA/GPE-coated strawberries were superior to the uncoated fruits during storage. Total mesophilic aerobic bacteria (TMAB) and yeast/mold counts in the uncoated strawberries were 2 and 2.68 log cfu/g at the start of storage, respectively, and 9.8 and 14.00 log cfu/g after 16 days of storage, respectively. Strawberries coated with the PVA solution with 2.5% ( w/v ) GPE showed 32% and 25% less TMAB and yeast/mold counts, respectively, at the end of storage. The PVA/GPE-coated strawberries showed significantly higher firmness compared to the control fruit. The PVA/GPE coating improved strawberry shelf life and functional properties.